Choice or Discovery An Exploration of Kierkegaard’s Theory of the Self (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
This paper explores the multifaceted nature of Kierkegaard's theory of the self. I begin with a description of Kierkegaard's conception of the self as consisting in the balance between three polarities (the finite – the infinite, necessity – freedom, the temporal – the eternal), held in tension. I then explore in detail Kierkegaard's notion of despair as a catalyst for the emergence of self-consciousness. This evolves into an exposition of his tripartite developmental schema, which comprises of the 'aesthetic', 'ethical' and 'religious' modes of existence. The orthodox reading of the contents that Kierkegaard's theory of the self is predicated upon the enactment of choice. This interpretation is challenged by Edward Mooney, who argues for a more complex reading wherein self-choice is coupled with self-reception. I conclude by considering Mooney's replacement of Kierkegaard's Christian God with a secular commitment to community.